RESPON HASIL PRODUKSI DUA VARIETAS TANAMAN KACANG TANAH (Arachis hypogaea L.) TERHADAP PENGGUNAAN BIOCHAR TEMPURUNG KELAPA - Mohammad Dwi Ferdy Pradana; Christa Dyah Utami; Ilham Muhklisin; Trisnani Alif; Devina Cinantya Anindita (Universitas Wahid Hasyim, 2026)
Peanut production in Jember Regency from 2020 to 2024 has experienced a significant decline. One of the contributing factors is the excessive use of inorganic fertilizers. Therefore, it is necessary to apply cultivation techniques that can restore soil fertility, such as biochar application. This study aimed to analyze the growth and yield responses of two peanut varieties to the application of coconut shell biochar. The research was conducted from June to November 2025 in Patemon Village, Pakusari District, Jember Regency, East Java, Indonesia. The experimental design used was a factorial randomized block design with two factors. The first factor was peanut variety, consisting of two levels: Katana 2 and Tala 1. The second factor was the dose of coconut shell biochar, consisting of five levels: 5, 10, 15, 20, and 25 tons ha⁻¹. The observed variables included plant height, number of leaf stalks, number of branches, pod weight per plot, number of filled pods, weight of fresh filled pods, weight of dry filled pods, and 100-seed weight per plot. The data were analyzed using analysis of variance (ANOVA). When significant differences were detected, further analysis was performed using the Least Significant Difference (LSD) test. The results showed that a biochar dose of 20 tons ha⁻¹ produced the highest number of filled pods, while a dose of 15 tons ha⁻¹ resulted in the highest fresh filled pod weight.